Reflective Pedagogy: Case Study of Organic Chemistry at the University of Muhammadiyah Semarang - Eko Yuliyanto; Fitria Fatichatul Hidayah; Enade Perdana Istyastono; Yosef Wijoyo; Titien Siwi Hartayu (Universitas Muhammadiyah Semarang, 2017)
The development of the modern age is a lot of changes in education is the paradigm of teacher-centered learninginto student-centered learning which has a very important role in maximizing its competence in classroom management. One of the lessons in chemistry education that has problems is organic chemistry courses. Based onthe reflections applied to teachers and students